Assessing equity of care across metastatic breast cancer treatment junctures: a multi-site retrospective cohort study - Carolyn Brown; Hyeun Ah Kang; Michael Johnsrud; Jamie Terry; Gury Doshi; Stephanie Broussard; Chinelo Orji (BMC Cancer)
Abstract Background Although inequality in the prevalence and mortality of metastatic breast cancer (mBC) have been documented, the contribution of non-clinical predictors along the care continuum remains unclear. This study aimed to identify determinants of disparities along the continuum of care among patients with mBC. Methods A retrospective cohort study of patients with mBC under the Medicare Oncology Care Model program was conducted with Texas Oncology Network data from July 2016 to June 2021 as well as the County Health Rankings and Roadmaps Data. Study outcomes were rates of completion and time to receipt of services across four key care junctures: (1) Diagnosis and Evaluation, (2) Treatment Plan Design, (3) Treatment Implementation, and (4) End-of-life Care. Race/ethnicity was the primary predictor variable and secondary predictors included sociodemographic and clinical characteristics (referred to as the Vulnerability Cluster). Bivariate analysis, multivariable logistic regression, and generalized linear models were employed. Results Among 460 patients included, mean age was 72.7 years and 98.7% were female; 73.7% were white, followed by 10.7% Hispanic, and 7.6% Black. Over 90% received services across the first three junctures. At End-of-life Care, only 14 (3.04%) received palliative care referral and 34.1% were enrolled in hospice, with an average length of stay (LOS) of 32.0 days. Adjusted analyses revealed significant racial/ethnic disparities in the End-of-life Care juncture, especially in hospice utilization. Compared to whites, blacks and Hispanics had shorter days to hospice enrollment, by 13.2% (Incidence Rate Ratio [IRR] = 0.868, 95% CI = 0.845–0.891, p < 0.001) and 34.8% (IRR = 0.652, 95% CI = 0.635–0.671, p < 0.001), respectively, and shorter LOS by 24.6 (IRR = 0.754, 95% CI = 0.645–0.882, p = 0.0004) and 25.3% (IRR = 0.747, 95% CI = 0.632–0.882, p = 0.0006), respectively. Other vulnerability cluster variables were predictive across care junctures. Conclusions The vulnerability cluster of variables, even in a Medicare population, were associated with the receipt and timeliness of care, especially at end-of-life among patients with mBC. More proactive and equitable care in mBC toward the end of their care journey is warranted.